2006
DOI: 10.1101/gad.349506
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism of AP-1 suppression through interaction of c-Fos with lamin A/C

Abstract: AP-1 (Activating Protein1The members of the Fos, Jun, ATF (Activating Transcription Factor), and MAF (Musculo Aponeurotic Fibrosarcoma) protein families are components of the dimeric AP-1 (Activating Protein 1) transcription factor complex. AP-1 participates in the regulation of a variety of cellular processes, such as cell proliferation, cell differentiation, neoplastic transformation, and apoptosis (Angel and Karin 1991; Karin et al. 1997;Eferl and Wagner 2003). AP-1 transcription factor activity is regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
176
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(191 citation statements)
references
References 50 publications
14
176
0
1
Order By: Relevance
“…Lamin A/C binds c-Fos, an interaction that correlates with decreased AP-1 DNA binding and transcriptional activation (45). Here the negative effect on gene expression is attributed to lamin A/C-mediated c-Fos sequestration, which reduces c-Fos/c-Jun heterodimer formation.…”
Section: Discussionmentioning
confidence: 97%
“…Lamin A/C binds c-Fos, an interaction that correlates with decreased AP-1 DNA binding and transcriptional activation (45). Here the negative effect on gene expression is attributed to lamin A/C-mediated c-Fos sequestration, which reduces c-Fos/c-Jun heterodimer formation.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly it has been reported that c-fos is sequestered in the nuclear envelope in a Lamin A/Cdependent manner, which effectively reduces AP-1 factor DNA binding activity. 33 It is tempting to speculate that continued AP-1-mediated transcription in the nuclear remnants is necessary for the increased BMP2 expression; 34 and that parakeratosis itself can alter keratinocyte terminal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, as part of the inner nuclear membrane, lamin A/C possesses additional properties such as interaction with transcription factors [3], distinct from other structural proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Because lamin A/C sequesters cFos at the nuclear envelope of fibroblasts and suppresses the DNA binding activity of transcription activator protein-1 (AP-1) by affecting cFos and cJun dimerization [3], reduced levels of lamin protein could have consequences on downstream transcription. If AV nodal myocytes, like other excitable neural cells, are particularly sensitive to AP-1 mediated transcriptional regulation, including caspase activation and stress-induced apoptosis [41], mutations that reduce lamin A/C levels could activate pro-cell death signals selectively in these specialized myocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation